The Murano Diptych. A Late Nineteenth-Century Quest for Early Byzantine Ivory Cover - Lidova, Maria A. (Actual Problems of Theory and History of Art, 2021)
The so-called Murano Diptych represents an important example of Early Byzantine ivory carving. The diptych once served as a Gospel book cover decorating both sides of a codex. On the one side, Christ enthroned surrounded by a Christological cycle was represented, while the carved surface of the other side was dedicated to the Mother of God and scenes taken from Apocrypha, narrating the story of Mary’s mother — St. Anne. This paper is dedicated to the history of research of the Murano Diptych and the first scholarly publications of this artifact. The contribution demonstrates that in the second half of the 19th century this artwork became the center of attention in the works of prominent scholars of Byzantine art, foremost Dmitry Ainalov and Josef Strzygowski. After the publication of the Ravenna relief by Raffaele Garrucci in 1880 a series of articles have come out, one after another, identifying other pieces of the diptych spread among various private collections and public displays. In this paper, I reconstruct the circumstances of these events, and the whereabouts of ivory fragments at the time of their first publication. Furthermore, I argue that the early scholarship on Murano diptych may be treated as a characteristic case in the development of art historical thought at the time when history of Byzantine art was acquiring its form as an academic discipline. This work was accomplished with financial support of RFBR grant № 21-012-41005 “Jerusalem and Understudied Apocrypha in Slavonic Translations: Textology, History, and Doctrines”.